Natural Pigments of Microbial Origin - Pailliè-Jiménez, Maria Elisa; Stincone, Paolo; Brandelli, Adriano (Frontiers in Sustainable Food Systems, 2020)
The world demands new solutions and products to be used as dyes for industrial applications. Microbial pigments represent an eco-friendly alternative as they can be produced in large amounts through biotechnological processes and do not present environmental risks, as they are easily decomposable. Moreover, some of these metabolites are recognized for their biological activities, which qualify them for potential uses as food colorants and nutraceuticals, protecting against degenerative diseases related with oxidative stress. Because of their genetic simplicity as compared with plants, microorganisms may be a better source to understand biosynthetic mechanisms and to be engineered for producing high pigment yields. Despite the origin of the pigmented microorganism, it seems very important to develop protocols using organic industrial residues and agricultural byproducts as substrates for pigment production and find novel green strategies for rapid pigment extraction. This review looks for the most recent studies that describe microbial pigments from microalgae, fungi, and bacteria. In particular, the underexploited tools of omics science such as proteomics and metabolomics are addressed. The use of techniques involving mass spectrometry, allows to identify different protein and metabolite profiles that may be associated with a variety of biotechnologically-relevant pathways of pigment synthesis.